Tertiary lymphoid structures in breast ductal carcinoma in situ correlate with adverse pathological parameters. Issue 5 (30th January 2023) - Zeng, Lixia; Koh, Valerie Cui Yun; Chen, Xiao‐Yang; Tan, Puay Hoon
Abstract : Aims: To investigate tertiary lymphoid structures (TLSs) in ductal carcinoma in situ (DCIS) of the breast and their correlation with pathological features, immune cell markers and clinical outcomes. Methods and results: Morphological identification of TLSs in 198 DCIS cases incorporated B and T cell zones with high endothelial venules. TLS positivity was defined as ≥ 1 TLSs in lesional areas, while TLS area percentage was divided into two categories: low (TLSs < 5%) and high (TLSs ≥ 5%). Previously reported biomarkers included ER, PR, HER2, CD68, CD163, CD4, CD8 and PD‐L1. TLSs were observed in 24.7% (49 of 198) of cases, with a mean diameter of 0.44 mm (median = 0.4 mm, range = 0.12–1.43 mm). TLSs were significantly associated with higher nuclear grade, presence of necrosis, hormone receptor negativity/HER2 positivity, triple negativity, tumour infiltrating lymphocytes (TILs) and immune related biomarkers such as FOXP3, CD163, CD4 and CD4/CD8 ratio (all P < 0.05). There were no significant associations between TLSs and recurrence, but a combination of TLSs high with FOXP3 +, CD4 high, CD4/CD8 ratio high and CD68 high individually, compared with all other combinations, disclosed significantly poorer disease‐free survival (DFS) for ipsilateral invasive recurrence (IIR) on both Kaplan–Meier and multivariable Cox regression analyses (all P < 0.05). Conclusions: TLSs in DCIS were associated with unfavourable prognostic features, TILs and immune cell markers in our study. TLSs high /FoxP3 +, TLSs high /CD4 high, TLSs high /(CD4/CD8) ratio high and TLSs high /CD68 high were independent factors for poorer DFS for IIR. Further exploration of the pathological significance of TLSs may provide a clinical basis for their recognition as an important structure and functional unit in the tumour immune microenvironment. Abstract :